Penerapan Keadilan Restoratif Pada Tindak Pidana Ringan di Kejaksaan Negeri Yogyakarta - Faisal Hadi Pramono; Laras Astuti (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2023)
Restorative justice practices are used to resolve criminal cases with minor or minor losses that do not have to be resolved through court but can be resolved at the Police and Prosecutor's Office stages. The resolution of the case can be carried out in a fair and balanced manner for the victim and the perpetrator, which is achieved through restorative justice by prioritizing restoration to its original state and improving community relations. Based on this, this article will discuss further the application of restorative justice to minor crimes at the Yogyakarta District Prosecutor's Office. This research uses a normative empirical method which refers to secondary data originating from the law and primary data originating from interviews with informants. The data processing process is carried out systematically and logically and processed in order to get a concise picture. Based on the research results, it can be concluded that the failure factor in implementing restorative justice at the Yogyakarta Police or Police level is caused by the parties attending the mediation meeting, but not proposing and/or not responding to the results of the agreement, one of the parties violating the agreement and community factors that have not removed the stigma of crime. what the perpetrator did. The resolution of minor crimes through restorative justice at the Yogyakarta District Prosecutor's Office is carried out with peace efforts by the Public Prosecutor so that an agreement is reached between the suspect and the victim.